(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text focuses on the production of Oficio de Isla in Havana, Cuba, a multimedia and intersemiotic show with extensive use of the performance and multiple scenarios of the port pier. The space, halfway between the city center and its outskirts, is full of historical meanings, allowing the public intense exchanges of sensitive and participatory experiences.